2004
DOI: 10.1897/02-645
|View full text |Cite
|
Sign up to set email alerts
|

Differential toxicity of copper, zinc, and lead during the embryonic development of Chasmagnathus granulatus (Brachyura, varunidae)

Abstract: Ovigerous females of the estuarine crab Chasmagnathus granulatus were exposed to copper (0.01 and 1 mg/L), zinc (0.05, 1, and 10 mg/L), or lead (0.01 and 1 mg/L) during early, late, or whole embryonic development. None of the assayed heavy metals produced a significant mortality of females, neither a decrease in the number of hatched larvae nor a decrease in the egg incubation time, but several morphological abnormalities were detected in hatched larvae. The abnormalities were classified in three categories: e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…arrest in the sea urchin, oyster, crab, sea squirt, and in insects (2,9,40,56,57,71). Clustering and GO analyses showed that at high concentrations, copper upregulated genes associated with cell fate determination and differentiation, embryonic development, and cell polarity, including IFN-related developmental regulator 1 (IFRD1), myeloid cell leukemia sequence 1 (MCL1), jagged 1 (JAG1), delta-like 1 (DLL1), tissue inhibitor of metalloproteinase 1 (TIMP1), MAFB, adenylate cyclase-associated protein 1 (CAP1), FYVE, RhoGEF, PH domain-containing 6 (FGD6), and IL-11 (Tables 4 and 5 and Supplemental Material, Additional Data File 5).…”
Section: Continuedmentioning
confidence: 99%
“…arrest in the sea urchin, oyster, crab, sea squirt, and in insects (2,9,40,56,57,71). Clustering and GO analyses showed that at high concentrations, copper upregulated genes associated with cell fate determination and differentiation, embryonic development, and cell polarity, including IFN-related developmental regulator 1 (IFRD1), myeloid cell leukemia sequence 1 (MCL1), jagged 1 (JAG1), delta-like 1 (DLL1), tissue inhibitor of metalloproteinase 1 (TIMP1), MAFB, adenylate cyclase-associated protein 1 (CAP1), FYVE, RhoGEF, PH domain-containing 6 (FGD6), and IL-11 (Tables 4 and 5 and Supplemental Material, Additional Data File 5).…”
Section: Continuedmentioning
confidence: 99%
“…While the presence or absence of phenotypic changes are reported, demonstration of the magnitude of the response in relation to exposure window and stressor dose is limited to a mere handful of studies (e.g. Degitz et al, 2000;Lavolpe et al, 2004;Hu et al, 2009;Yuan et al, 2011). Therefore, while typical studies of critical windows are useful for detecting periods of plasticity or susceptibility, they are limited in their ability to fully appreciate the phenotypic changes displayed by a developing animal.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent organic pollutants can induce morphological deformities in peneids or crabs (Weis et al, 1987;Betancourt-Lozano et al, 2006). Heavy metals could also induce deformities in brachyura larvae (Lavolpe et al, 2004).…”
mentioning
confidence: 99%